Impact Analysıs Of Socıal Medıa, Brand Image, Qualıty Of Coffee Drınkıng Products Influence Purchase Decısıons In Islamıc Economıc Perspectıve - Paulina Lubis; Rafiqi Rafiqi; Fitri Widiastuti; Afi Parnawi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The changing trend of the coffee beverage business is currently taking place quite rapidly. Moving from just an ordinary coffee drinking activity which has now become part of a lifestyle, business people are tempted to start and engage in this business. In running the coffee drink business today, the role of social media is very necessary which in turn has an impact on product sales results. Consumers will see the information conveyed through social media on the quality and brand image conveyed by product sellers, and this is where the shape of the decision to buy coffee drink products emerges. The specific purpose of this study is to describe the driving factors of consumers in making purchasing decisions for contemporary coffee drink products in terms of aspects of social media, brand image, product quality from an Islamic economic perspective, where the Islamic economic system refers to the principles of ownership, justice, freedom, and togetherness in the distribution of social economic welfare. By using a quantitative method, a list of questions was distributed online to 200 students both from within Jambi University and outside the Jambi University campus. The primary data collected will be processed using SEM-SmartPLS. The targeted finding is a model that can be used to see the influence of social media, brand image and product quality of contemporary coffee drinks on purchasing decisions in an Islamic economic perspective. brand image and maintain product quality in the future